Relasi Nasionalisme Etnik, Nasionalisme Negara dan Nasionalisme Kewarganegaraan di Papua - Susanto T. Handoko; La Ode Hasirun (Jurnal Sejarah Citra Lekha, 2019)
This article aims to discuss the dynamics of relations between ethnic nationalism, civic nationalism and state nationalism in the Land of Papua. The growth and development of Papuan ethnic nationalism since the integration of Papua into reform was caused by Indonesian state policies. Historical method is used in this research. The research approach is a qualitative approach to phenomenological research design. Strengthening Papuan ethnic nationalism due to the Central Government's (Jakarta) policies that were not fully accepted by indigenous Papuans. The Papuan people felt marginalized and discriminated against in the process of development in both the political, economic, social and cultural fields, especially during the New Order government. Papuan ethnic nationalism is characterized by demands for independence from the Indonesian state and instrumentalization of ethnicity for political purposes. Ethnic nationalism eventually shifts the civic and or state nationalism as part of the Indonesian state.